REGULATION ECOSYSTEM SERVICES IN A WATERSHED IN THE SEMI-ARID OF BRAZIL - de Oliveira, Paulo Jerônimo Lucena; Guedes, Jânio Fernandes; Costa, Diógenes Felix da Silva (Mercator, 2023)
Human pressures on ecosystems from the use and suppression of vegetation cover cause negative actions on biodiversity, impacting nature and the ecosystem services provided by the same. The focus of this research is to evaluate the ability to provide Ecosystem Services in the Seridó River Basin (RN / PB). Modeling techniques were applied from USLE, in addition to vegetation and organic carbon indices. The results showed that the highest values ​​of NDVI are in areas of higher elevation and slope, and the lowest values ​​found in flat areas. Six classes of land use were identified, namely: Water bodies, urban area, Pasture and exposed rock, Caatinga Subarbustiva, Subarbórea and Arbórea. As a result, the areas of greatest relevance for providing Organic Carbon stock services are in the highest areas, with the areas with the greatest erosion control located in escarpment areas.    Key words : Ecosystem Services; Modeling; Caatinga; Semiarid; Hydrographic basin.